2018
DOI: 10.1038/s41598-018-26358-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cry2Aa, a Bacillus thuringiensis insecticidal protein in transgenic pigeon pea confers resistance to gram pod borer, Helicoverpa armigera

Abstract: Pigeon pea is an important legume infested by a plethora of insect pests amongst which gram pod borer Helicoverpa armigera is very prominent. Imparting resistance to this insect herbivore is of global importance in attaining food security. Expression of insecticidal crystal proteins (ICP) in diverse crops has led to increased resistance to several pests. We report in this paper, expression of Cry2Aa in transgenic pigeon pea and its effectiveness towards H. armigera by employing Agrobacterium-mediated in planta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 32 publications
(39 reference statements)
1
38
0
1
Order By: Relevance
“…Bacillus thuringiensis ( Bt ) insecticidal proteins (ICPs) that encode a delta endotoxin have proved to be the most suitable and safe alternative to chemical pesticides. The major emphasis of our group has been in the development of transgenics in pigeonpea for mitigation of the pod borer H. armigera using a tissue culture‐independent in planta transformation strategy . Several other research groups have also produced transgenic pigeonpea with the development of diverse Bt genes .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Bacillus thuringiensis ( Bt ) insecticidal proteins (ICPs) that encode a delta endotoxin have proved to be the most suitable and safe alternative to chemical pesticides. The major emphasis of our group has been in the development of transgenics in pigeonpea for mitigation of the pod borer H. armigera using a tissue culture‐independent in planta transformation strategy . Several other research groups have also produced transgenic pigeonpea with the development of diverse Bt genes .…”
Section: Introductionmentioning
confidence: 99%
“…Diet feed assays have shown that there was severe growth inhibition among the survivor larvae . This prompted scientists to exploit this gene as an alternative to cry1Ac to mitigate pod borer . These two ICPs show potent activity against H. armigera and apparently target different receptors in the insect gut.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations